Spatial Building Typology (Volume 2) Vacant Heritage: Police Real Estate | The Netherlands - Zijlstra, Hielkje; Fischer, Lucca; van Asselt, Noah; de Gouw, Tjeu (2022)
The Dutch Police is one of the largest owners of public real estate in the Netherlands. From police station to forensic laboratory, from listed buildings in the centre of The Hague to large-scale facilities next to the motorway in Driebergen: the task of accommodating the Police is as diverse as it is challenging. Themes such as innovation and sustainability, health and safety, as well as identity, flexibility and affordability are all of relevance for the Police's accommodation strategy. Efforts are being made to strike a new balance between the physical, mobile and digital workplace.Since the formation of the National Police, there has been an enormous challenge to accommodate the organization. In realizing this task, the police has the ambition to raise the quality of police buildings as well as the experience users have in the buildings. At the same time, the police is at the heart of an ever changing society: The accommodation needs to meet the requirements posed by several developments such as the energy transition, climate change and digitization. How do these developments influence the task of future-proofing (cultural) heritage? Which role can our heritage buildings play in these transitions?The key lies in our present actions coupled with the lessons of the past. Different approaches on Built Heritage will open our eyes and help with today's issues. To see what is valuable. Will the decisions made in the past be our strength or pitfall? How will objects developed in the past, exposed to today's spatial developments, help us? Through the power of imagination, the Studio Vacant heritage from Heritage and Architecture proudly reveals many possibilities.